Análisis de la acción de protección a partir de la entrada en vigencia de la Constitución de la República del ecuador del 2008 y sus principales fortalezas y debilidades - Chávez Moreno, Marcela Raquel (2015)
The Constitution of the Republic of 2008 under the figure of reformulated to give rise to a constitutional guarantee of the features that coated the doctrine has granted effective protection mechanisms for protecting rights. This implies a radical change of state from a liberal view towards one of law, and beyond, to a State Constitutional Rights and Justice in the Supreme Standard is direct and immediate implementation by all judges, in turn, become providers of constitutionality. The precautionary nature of residual or subsidiarity protective action makes it feasible to become directly, not only when there is a better and more beneficial for the person who intends to demand judicial process, it is understood that this action is appropriate only when affected his constitutional rights has no other means of legal defense; However, Article 88 of the Constitution of the Republic is not given to the action of the character of residual protection or subsidiary, as apparently does the Law and Constitutional Guarantees of Jurisdictional Control and must prevail in this case will constituent over any contradiction in a secondary standard or ambiguity of the text; Moreover, and as a fundamental criterion should observe the principle of supremacy of the Constitution stated in Article 424 of the Constitution. To take protective action by the constituent expected results, it is essential that an evolution occurring in the role of the judge, since the formalism has been superseded by the current neoconstitucionalista, whose influence is evident in the 2008 Constitution. But it also plays a role that serves the law judge tool for the realization of the effective guarantee and protection of rights, to be developed by the same guarantees and protectionist state program, establishing parameters for admissibility, admission criteria, methods interpretation, and procedural rules necessary for proper learning process warranty, being a legal novelty. With these elements, we proceeded to develop this research project their share of Literature Review has been the history of protective action. Shape Evolution of Amparo. Nature of protective action.Subject protective action.Features protective action; origin, inadmissibility and eligibility of protective action, the procedural step of protective action; Formal structure and content of the judgment. Finally in the field have seen the strengths and weaknesses of the system of administration of justice in constitutional guarantees, and specifically around protective action, understanding what are the criteria used by the judges to admit or reject are what action can be determined, in turn, the analysis of the interpretation made to the rules on admissibility and eligibility contained in Articles 10, 40 and 42 of the Organic Law on Jurisdictional Guarantees and Constitutional Control